2020
DOI: 10.1186/s12915-020-0764-z
|View full text |Cite
|
Sign up to set email alerts
|

DDX39B interacts with the pattern recognition receptor pathway to inhibit NF-κB and sensitize to alkylating chemotherapy

Abstract: Background: Nuclear factor-κB (NF-κB) plays a prominent role in promoting inflammation and resistance to DNA damaging therapy. We searched for proteins that modulate the NF-κB response as a prerequisite to identifying novel factors that affect sensitivity to DNA damaging chemotherapy. Results: Using streptavidin-agarose pull-down, we identified the DExD/H-box RNA helicase, DDX39B, as a factor that differentially interacts with κB DNA probes. Subsequently, using both RNA interference and CRISPR/Cas9 technology,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…It was identified that DDX39B may possibly be a target gene of hsa-miR-4488 according to the multiMiR database. It has been reported that DDX39B interacts with the pattern recognition receptor pathway to inhibit NF- κ B signaling [ 32 ]. In the present study, hsa-miR-4488 was significantly upregulated in DM-ILD-MDA5 Ab(+) when compared to DM-nonILD-MSA16(-) and HC, suggesting that miR-4488 may contribute to systemic inflammation in DM-ILD-MDA5 Ab(+) by upregulating NF- κ B signaling through repression of DDX39B.…”
Section: Discussionmentioning
confidence: 99%
“…It was identified that DDX39B may possibly be a target gene of hsa-miR-4488 according to the multiMiR database. It has been reported that DDX39B interacts with the pattern recognition receptor pathway to inhibit NF- κ B signaling [ 32 ]. In the present study, hsa-miR-4488 was significantly upregulated in DM-ILD-MDA5 Ab(+) when compared to DM-nonILD-MSA16(-) and HC, suggesting that miR-4488 may contribute to systemic inflammation in DM-ILD-MDA5 Ab(+) by upregulating NF- κ B signaling through repression of DDX39B.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of DDX39B has been reported to promote resistance to alkylating chemotherapy in glioblastoma cells. 37 Similarly, DDX19 impaired type I interferon production, resulting in suppression of encephalomyocarditis virus replication. 38 In this study, we discovered that DDX49 was overexpressed in lung adenocarcinoma tissues and cell lines in comparison with paracancerous tissues and normal cells.…”
Section: Discussionmentioning
confidence: 99%
“…DExD RNA helicases play great roles in cancers. Loss of DDX39B has been reported to promote resistance to alkylating chemotherapy in glioblastoma cells 37 . Similarly, DDX19 impaired type I interferon production, resulting in suppression of encephalomyocarditis virus replication 38 .…”
Section: Discussionmentioning
confidence: 99%
“…An investigation used CRISPR-Cas9 to knockdown DDX39B (DExD-box helicase 39B) gene in U87MG cell line and found that down regulation of the expression of angiogenesis-related factors [ 70 ]. Similarly, it has been shown that CRISPR-Cas9 mediated knockdown of Notch1 gene significantly impaired expression of angiogenesis and related factors in response to radiotherapy in U87MG and U251 cells [ 33 ].…”
Section: Use Of Crispr-cas9 Editing For Identifying Genetic Regulators Of Angiogenesis In Gbmmentioning
confidence: 99%